Teaching Basic Life Support to schoolchildren: quasi-experimental study - Ana Carolina Carraro Tony; Fábio da Costa Carbogim; Daniela de Souza Motta; Kelli Borges dos Santos; Amanda Aparecida Dias; Andyara do Carmo Pinto Coelho Paiva (Universidade de São Paulo, 2020)
Objective: to evaluate the knowledge of basic education students before and after educational intervention on Basic Life Support in a situation of adult cardiorespiratory arrest. Method: quasi-experimental study conducted with 335 students from three elementary schools. Data was collected using an instrument that captured sociodemographic data and knowledge about Basic Life Support. Subsequently, they were analyzed by descriptive and analytical statistics. Results: students' knowledge in the post-test (p <0.05) was significantly higher than in the pre-test. The average of the pre-test scores was 4.12 ± 1.7 and, in the post-test it was 6.53 ± 1.9 (p = 0.00). Conclusion: the results demonstrated effectiveness of the intervention with the expansion of knowledge about Basic Life Support in cardiorespiratory arrest. The results reinforce the importance of Nursing in health education actions in elementary schools.